Preparation of L-Proline Chiral Bonded Silica Gels and Their Application in Beer - Yuan, Shizhen; Zhang, Kehua; Xia, Jingjing (Asian Journal of Chemistry, 2014)
The chiral L-proline-silica gel was prepared by using silica gel with allyl glycidyl ether. When the coverage of L-proline surpassed 30 %, the adsorption rates of haze-active protein decreased. The benefits of L-proline-silica gel in beer stabilization were shown to specifically adsorb haze-active proteins and hardly affect beer foam stability.